A Nitric Oxide-Donor Furoxan Moiety Improves the Efficacy of Edaravone against Early Renal Dysfunction and Injury Evoked by Ischemia/Reperfusion. (5th March 2015) - Chiazza, Fausto; Chegaev, Konstantin; Rogazzo, Mara; Cutrin, Juan C.; Benetti, Elisa; Lazzarato, Loretta; Fruttero, Roberta; Collino, Massimo
Abstract : Edaravone (5-methyl-2-phenyl-2, 4-dihydro-3H-pyrazol-3-one, EDV) is a free-radical scavenger reduces organ ischemic injury. Here we investigated whether the protective effects of EDV in renal ischemia/reperfusion (I/R) injury may be enhanced by an EDV derivative bearing a nitric oxide- (NO-) donor furoxan moiety (NO-EDV). Male Wistar rats were subjected to renal ischemia (45 minutes), followed by reperfusion (6 hours). Administration of either EDV (1.2–6–30  µ mol/kg, i.v.) or NO-EDV (0.3–1.2–6  µ mol/kg, i.v.) dose-dependently attenuated markers of renal dysfunction (serum urea and creatinine, creatinine clearance, urine flow, urinary N-acetyl- β -D-glucosaminidase, and neutrophil gelatinase-associated lipocalin/lipocalin-2). NO-EDV exerted protective effects in the dose-range 1.2–6  µ mol/kg, while a higher dose (30  µ mol/kg) was needed to obtain protection by EDV. Both EDV and NO-EDV modulated tissue markers of oxidative stress and lipid peroxidation. NO-EDV, but not EDV, activated endothelial NO synthase (NOS) and blunted I/R-induced upregulation of inducible NOS, secondary to modulation of Akt and NF- κ B activation, respectively. Besides NO-EDV administration inhibited I/R-induced IL-1 β, IL-18, IL-6, and TNF- α overproduction. Overall, these findings demonstrate that the NO-donor moiety contributes to the protection against early renal I/R injury and suggest that NO-donor EDV codrugs are worthy of additional study as innovative pharmacological tools.